(untitled) (Revista Sistemas de Producción Agroecológicos, 2023)
The growing demand for animal-derived foods in the world’s fastest growing economies has significantly increased livestock production, with the help of important technological innovations and structural changes in the sector. The semi-intensive system in bovine production is one of the available techniques for intensifying the fattening of bovines on pasture, where the objective of Semiconfinement is to increase zootechnical results such as daily weight gain, meat production per hectare, performance and the level casing finishing. An important point in this management is the correct supply of the concentrated ration, this must be done daily in the correct quantities per batch of animals, always at the same times, in addition the implementation of by-products from agricultural production helps to improve aspects of good nutrition. , reduce environmental pollution and improve the economic factor for our farmers. The following describes the improvement of a bovine production system thanks to the advice of the Cosmopolitana Agroecológica Ltda company of the Restrepo municipality, Meta, where it was identified that the production obtained good results according to the diet used, also implementing by-products and thus generating better profitability.